Searching for the dark photon at the Future Circular Lepton Collider - X.G. Wang; A.W. Thomas (Physics Letters B)
In the context of future electroweak precision measurements at the Future Circular Lepton Collider (FCC-ee), we consider recent proposals aimed at finding signatures of physics beyond the Standard Model. In particular, we focus on recent novel suggestions for very precise direct measurements of αem(MZ2). It is shown that at a level of precision of order 10−5, the effects of a dark photon may be very significant.